Study of the performance of a thermophilic biological methanation system. (February 2017) - Guneratnam, Amita Jacob; Ahern, Eoin; FitzGerald, Jamie A.; Jackson, Stephen A.; Xia, Ao; Dobson, Alan D.W.; Murphy, Jerry D.
Highlights: Biological methanation was assessed at 55 and 65 °C with mixed culture. The efficiency were better at 65 °C than 55 °C. Methane content of ca. 90% was achieved at productivity of 0.45 L CH4 /L reactor/day. Reseeding of the process is required as when inoculum ages, efficiencies decrease. Methanothermobacter species dominate in the ex-situ methanation community. Abstract: This study investigated the operation of ex-situ biological methanation at two thermophilic temperatures (55 °C and 65 °C). Methane composition of 85–88% was obtained and volumetric productivities of 0.45 and 0.4 L CH4 /L reactor were observed at 55 °C and 65 °C after 24 h respectively. It is postulated that at 55 °C the process operated as a mixed culture as the residual organic substrates in the starting inoculum were still available. These were consumed prior to the assessment at 65 °C; thus the methanogens were now dependent on gaseous substrates CO2 and H2 . The experiment was repeated at 65 °C with fresh inoculum (a mixed culture); methane composition and volumetric productivity of 92% and 0.46 L CH4 /L reactor were achieved in 24 h. Methanothermobacter species represent likely and resilient candidates for thermophilic biogas upgrading.